Synthesis of a C2-aryl-pyrrolo[2, 1-c][1, 4]benzodiazepine monomer enabling the convergent construction of symmetrical and non-symmetrical dimeric analogs. Issue 30 (22nd July 2015) - Kolakowski, Robert V.; Young, Thomas D.; Howard, Philip W.; Jeffrey, Scott C.; Senter, Peter D.
Graphical abstract: Abstract: We disclose the synthesis of a versatile C2-aryl-pyrrolo[2, 1- c ][1, 4]benzodiazepine (PBD) monomer that enables the late-stage diversification and synthesis of PBD dimers. The monomer unit was elaborated and dimerized utilizing different tethers to yield symmetric and non-symmetrical C2-aryl-PBD dimers. The dimers were tested for cytotoxic activity on a number of cancer cell lines and showed potent cytotoxicity in the nanomolar to picomolar range. The synthesis of PBD monomers enables the modular construction of PBD free drugs and drug-linkers that may have application for the development of antibody–drug conjugations.